Thoracic degenerative spondylolisthesis-associated myelopathy: A case report. Issue 21 (28th May 2021) - Wang, Huafeng; Lin, Fengfei; Liang, Guiqing; Liu, Boling; Lin, Yuhan
Abstract: Rationale: The thoracic spine is stabilized in the anteroposterior direction by the rib cage and the facet joints, thus thoracic degenerative spondylolisthesis is very uncommon. Here, we report a rare case of thoracic degenerative spondylolisthesis in which the lower thoracic region was the only region involved. Patient concerns: We present the case of a 56-year-old Chinese female who suffered from thoracic degenerative spondylolisthesis. She had a 2-year history of gait disturbance and bilateral lower-extremity numbness. The initial imaging examinations revealed Grade I anterior spondylolisthesis and severe cord compression, as well as bilateral facet joint osteoarthritis at T11/12. Diagnosis: The patient was diagnosed with thoracic degenerative spondylolisthesis-associated myelopathy. Interventions: She underwent a posterior decompression with transforaminal thoracic interbody fusion (TTIF) at T11/12. Outcomes: The patient recovered well after the operation, and MRI at 12-month follow-up revealed that spinal cord compression was relieved and high signal intensity in T2-weighted image was improved. Lessons: To the best of our knowledge, this is the first reported case of thoracic degenerative spondylolisthesis in which the lower thoracic region was the only region involved. Disruption of joint capsule, instability with micromotion, and degenerative disc may contribute to this rare disease. Posterior decompression with posterolateral fusion or TTIF were the main treatment modalities, however, TTIF has its unique advantages because of sufficient decompression, immediate stability and high fusion rate.